Fundamento para todos. Editorial - Gamella González, David J. (MISOSTENIDO, 2024)
Russell en 1948 advertía que “todo conocimiento humano es incierto, inexacto y parcial”. Bayés, en 2023, recogiendo sus palabras, reclama pensamiento crítico como antídoto ante cualquier dogmatismo. Siguiendo este hilo, nos ponemos del lado de la investigación. Sin ella no hay musicoterapia, como tampoco hay arte, literatura, periodismo, justicia o medicina. Musicoterapia e investigación son dos elementos de un mismo ecosistema. Como el árbol enriquece la tierra, ésta le nutre y sustenta.
A foundation for all. Leading article
Russell, in 1948, warned that "all human knowledge is uncertain, inaccurate, and partial." In 2023, Bay is calling for critical thinking as an antidote to any dogmatism. Following this thread, we take the side of research. Without it, there is no music therapy, just as there is no art, literature, journalism, justice or medicine. Music therapy and research are two elements of the same ecosystem. As the tree enriches the earth, it nourishes and sustains it.
Keywords: editorial; leading article; MISOSTENIDO